Evaluation of antioxidant activity of Malus domestica fruit extract from Kashan area - Sara Jelodarian; Abdolrasoul Haghir Ebrahimabadi; Ahmad Khalighi; Hossain Batooli (Mashhad University of Medical Sciences, 2012)
Objective: Antioxidants are considered as the main factors in the inhibition of unwanted oxidation reactions. Materials and Methods: In this research the antioxidant potential of the fresh fruits of 4 cultivars (A to D) of Malus domestica (M. domestica) cultivated in the Kashan, Qamsar area was evaluated. The antioxidant activity of the samples were evaluated using two complementary antioxidant assays: 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and β-carotene/linoleic acid tests and the results were compared with the synthetic standard antioxidant butylated hydroxytoluene (BHT). Results: Total phenolic contents of the samples are also estimated by Folin-Ciocalteu's phenol test. In both DPPH β-carotene/linoleic acid tests in the concentration of 2 mg/ml, only samples from cultivar A showed moderate antioxidant activity with 63.92±0.42 and 6.02±0.03 inhibition percentages, respectively and other samples were weakly active. Conclusion: The Folin-Ciocalteu's phenol test was also showed very little phenolic compounds for the fruits. In conclusion, weak antioxidant activity was estimated for the studied apple cultivars.